Molecular Mechanism and Approach in Progression of Meningioma - Shao, Zhiwei; Liu, Lihong; Zheng, Yanghao; Tu, Sheng; Pan, Yuanbo; Yan, Sheng; Wei, Qichun; Shao, Anwen; Zhang, Jianmin (Frontiers in Oncology, 2020)
Meningioma is the most common tumor of the central nervous system, most of which is benign. Even after complete resection, a high rate of recurrence of meningioma is observed. From in-depth study of its pathogenesis, it has been found that a number of chromosomal variations and abnormal molecular signals are closely related to the occurrence and development of malignancy in meningioma, which may provide the theoretical basis and potential direction for accurate and targeted treatment. We have reviewed advances in chromosomal variations and molecular mechanisms involved in the progression of meningioma, and have highlighted the association with malignant biological behavior including cell proliferation, angiogenesis, increased invasiveness, and inhibition of apoptosis. In addition, the chemotherapy of meningioma is summarized and discussed.